EPSPS gene amplification confers resistance to glyphosate resistant populations of Hordeum glaucum Stued (northern barley grass) in South Australia. Issue 4 (2nd December 2019) - Adu‐Yeboah, Patricia; Malone, Jenna M; Fleet, Benjamin; Gill, Gurjeet; Preston, Christopher
Abstract: BACKGROUND: Glyphosate failed to control two populations of Hordeum glaucum (northern barley grass) along a fence line and around stockyards near Arthurton on the Yorke Peninsula, South Australia after more than a decade of regular use of glyphosate. These were investigated to confirm resistance and to determine resistance mechanisms. RESULTS: Dose–response experiments confirmed resistance of these populations to glyphosate with resistance levels of 2.8–6.6‐fold compared with two susceptible populations. Shikimate assays confirmed resistance to glyphosate with less shikimate accumulation in the resistant populations compared with the susceptible populations. Quantitative PCR of genomic DNA showed increased gene copy number in the resistant populations with 9–11‐fold more copies of EPSPS compared with the susceptible populations, suggesting resistance is likely conferred by gene amplification. CONCLUSION: This study identified the first examples of glyphosate resistance in the grass species H. glaucum with resistance associated with EPSPS gene amplification. © 2019 Society of Chemical Industry Abstract : Glyphosate failed to control some populations of Hordeum glaucum along fence lines in South Australia. This study identified EPSPS gene amplification as the mechanism conferring resistance in these populations.